2016
DOI: 10.2337/dc15-2298
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Preload Enhances the Glucose-Lowering Efficacy of Vildagliptin in Type 2 Diabetes

Abstract: OBJECTIVENutrient "preloads" given before meals can attenuate postprandial glycemic excursions, at least partly by slowing gastric emptying and stimulating secretion of the incretins (i.e., glucagon-like peptide-1 [GLP-1] and glucose-dependent insulinotropic polypeptide [GIP]). This study was designed to evaluate whether a protein preload could improve the efficacy of the dipeptidyl peptidase-4 (DPP-4) inhibitor vildagliptin to increase incretin concentrations, slow gastric emptying, and lower postprandial gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 31 publications
3
60
3
Order By: Relevance
“…Unfortunately, GIP receptor antagonists suitable for human use are not currently available. Although stimulation of endogenous GLP-1 secretion has been shown to potentiate glucose-lowering by DPP-4 inhibitors (18,19), recent studies employing the GLP-1 receptor antagonist, exendin (9 -39), suggest that GLP-1 accounts for only ϳ50% of the insulinotropic and glucose-lowering effects associated with DPP-4 inhibition in patients with type 2 diabetes (16,17). Several other DPP-4 substrates (eg, oxyntomodulin, PACAP and SDF-1␣ (38)) may, like the incretin hormones, contribute to the lowering of glucose by VILD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, GIP receptor antagonists suitable for human use are not currently available. Although stimulation of endogenous GLP-1 secretion has been shown to potentiate glucose-lowering by DPP-4 inhibitors (18,19), recent studies employing the GLP-1 receptor antagonist, exendin (9 -39), suggest that GLP-1 accounts for only ϳ50% of the insulinotropic and glucose-lowering effects associated with DPP-4 inhibition in patients with type 2 diabetes (16,17). Several other DPP-4 substrates (eg, oxyntomodulin, PACAP and SDF-1␣ (38)) may, like the incretin hormones, contribute to the lowering of glucose by VILD.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 appears to mediate about 50% of the insulinotropic and glucose-lowering effects associated with DPP-4 inhibition (16,17). Furthermore, stimulation of GLP-1 secretion (eg, by small macronutrient preloads ingested before the main meal) potentiates the lowering of blood glucose by DPP-4 inhibitors (18,19).…”
mentioning
confidence: 97%
“…The same study also found WPH independently inhibited DPP-IV activity, though the effect was less potent than the combined therapy. A combined therapy that included a preload of 25 g WPI 60 min post administration of another gliptin - vildagliptin - in patients with T2DM on metformin resulted in significant increases in the levels of GIP, GLP-1 and decreases in postprandial glycemia and slower gastric emptying [52]. The study also tested WPI preloads again in the same patients on metformin without vildagliptin and found significant reductions in the glycemic peak, increased insulin and total and intact GLP-1 and GIP compared to control.…”
Section: Insulinotropic Effects Of Wheymentioning
confidence: 99%
“…Hence, the effect of DPP-4 inhibition on gastric emptying is of interest. Although Nauck et al (9) found no effect measured by a breath test (9), there is probably a modest slowing (10,19), albeit much less than that induced by short-acting GLP-1 agonists (16). Gastric emptying is also a determinant of the glycemic response to DPP-4 inhibition (19,20), and strategies that slow gastric emptying and stimulate GLP-1 secretion, such as whey preloads (19), potentiate glucose lowering.…”
Section: Dpp-4 Inhibition and The Known Unknownmentioning
confidence: 99%